Continuous Availability in Replicated Program - Hatkar, Tarikesh; Dhikale, Bhushan; Durugkar, Santosh (International Journal of Computer Sciences and Engineering, 2014)
One of the main reasons for income loss in enterprises that is usually addressed by providing redundant software and hardware is Service downtime. A way to provide software redundancy is to create a replica of the state of a program in execution to a set of replicas such as, when the primary fails. The place of the formerly running application occurrence is presumed by one of the replicas. A prototype of continuously available replica programs is provided, in case of failure of primary a replica takes over the functionality without any service downtime. Thus, the costly task of starting a new application occurrence on the other machine is avoided. When the mail server get disconnected, design offline email gears service. Or email gears are being developed To encounter the network failure . All email operations can be performed even if the network fails.